EFFORTS TO DEVELOP SHARIA-COMPLIANT AND PROFESSIONAL CIVIL SERVANT COOPERATIVES - Nilam Sari (Centre for Adat and Legal Studies of Aceh Province (CeFALSAP), 2022)
This article exposes the model and format of civil servant cooperative (KPN) that correspond to sharia and professional system, factors which become obstacle development of KPN in surroundings of UIN Ar-Raniry, and steps that should be taken to reformatting the existed system in order to correspond to sharia principles and more professional. Data collection methods by in depth interview and comparative study (site visit). Respondent (interview) was Head of Department of Cooperative Province which exist in Aceh, administrator of KPN Muamalah, and other KPN that presence in Aceh. Results of study indicated that among of ideal format of KPN was its operational activity must be run correspond to sharia principle, the organization structure accord with need and have a distinct of function, have a good planning, instruction of manager is clear, a good controlling system, the modern administration and have a clear business development strategy and capacity building of continuous member. Among of things that hinder the development of KPN in surroundings of UIN was participation level of member is still low, socialization not yet optimal, not hol collaboration with sharia cooperative inside or outside the campus, caretaker and organizer were less professional in the field, still relied on profit 1% of loan of member without other business. Efforts can be done to reformatting and developing KPN in surroundings of UIN Ar-Raniry was: functioning the role of DPS which filtering the activities of cooperative business, select to competence caretaker and willing to be organizer the cooperative and develop it. Broaden the sector cooperative business and carried out promotion facilities in business unit. Applied good cooperate governance (GCG) system and ordering the modern cooperative management such as bookkeeping administration and the information system, and be ready audited.